Bone histomorphometric changes in children with rheumatic disorders on chronic glucocorticoids. Issue 1 (December 2016) - Harrington, Jennifer; Holmyard, Douglas; Silverman, Earl; Sochett, Etienne; Grynpas, Marc
Abstract Background Rheumatic diseases are associated with an increased fracture risk. The tissue level characteristics of the bone involvement in children have not been well elucidated. Our objectives were to describe the bone micro-architectural characteristics in children with rheumatic diseases on chronic glucocorticoids, and to determine associations between micro-architectural findings with clinical and radiological variables. Methods Children on chronic glucocorticoids for an underlying rheumatic disease were referred for evaluation of bone fragility given the presence of vertebral compression fractures. A trans-iliac bone biopsy was performed as part of the clinical assessment. Histomorphometric analysis and quantitative backscattered electron imaging (qBSE) of the biopsy samples were undertaken. Results Data of 15 children (14.0 ± 3.2 years) with a duration of glucocorticoid exposure of 6.2 ± 4.1 years and average prednisone dose of 14.1 ± 6.2 mg/m2 /day were assessed. Histomorphometric analyses demonstrated significant decrease in trabecular thickness (p = 0.01), osteoid thickness (p < 0.01), osteoblast surface (p = 0.02) and increase in trabecular separation (p = 0.04) compared to published age-matched normative data. Severity of the trabecular deficit was correlated to glucocorticoid dose, height and body mass index Z score, but not bone mineral density or measures of disease activity. Using qBSE to measure bone mineralization, the subjects were shown to have a heterogeneous and hypermineralized profile, with higher cumulative glucocorticoid dose being associated with greater mineralization (p < 0.01). Conclusions In children with rheumatic diseases presenting with vertebral fractures, there is evidence of abnormal bone matrix mineralization and impairments of bone micro-architecture that correlate to glucocorticoid dose.